Tantangan dan Peluang Dunia PR di Era Kecerdasan Buatan : Sebuah Tinjauan Literatur - Mustikaningsih, Marlina; Fahrudin, Atef (Universitas Majalengka, 2024)
This study focuses on the challenges and opportunities of implementing artificial intelligence (AI) in the field of Public Relations (PR). The main issues addressed are the lack of technical understanding among PR practitioners and the ethical and privacy concerns arising from AI usage. The purpose of this study is to analyze how AI can enhance operational efficiency and the effectiveness of communication strategies, as well as to identify new metrics introduced by AI. The method used is a literature review from various academic and industry sources, including scientific journals, books, industry reports, and online articles. Data analysis was conducted using a thematic analysis approach, where information from various sources was organized into key themes relevant to the research topic. The results indicate that AI offers significant potential in enhancing PR effectiveness through real-time sentiment analysis, digital content engagement rate, and predictive analytics. Case studies from companies like Apple, Coca-Cola, IBM, and Sephora illustrate how AI can be used to improve audience interaction, user engagement, and PR campaign ROI.